Magnesium sulphate for treatment of severe tetanus: a randomised controlled trial. - Thwaites, C; Yen, L; Loan, H; Thuy, T; Thwaites, G; Stepniewska, K; Soni, N; White, N; Farrar, J (2006)
BACKGROUND: The most common cause of death in individuals with severe tetanus in the absence of mechanical ventilation is spasm-related respiratory failure, whereas in ventilated patients it is tetanus-associated autonomic dysfunction. Our aim was to determine whether continuous magnesium sulphate infusion reduces the need for mechanical ventilation and improves control of muscle spasms and autonomic instability. METHODS: We did a randomised, double blind, placebo controlled trial in 256 Vietnamese patients over age 15 years with severe tetanus admitted to the Hospital for Tropical Medicine, Ho Chi Minh City, Vietnam. Participants were randomly assigned magnesium sulphate (n=97) or placebo solution (n=98) intravenously for 7 days. The primary outcomes were requirement of assisted ventilation and of drugs to control muscle spasms and cardiovascular instability within the 7-day study period. Analyses were done by intention to treat. This trial is registered as an International Standard Randomised Clinical Trial, number ISRCTN74651862. FINDINGS: No patients were lost to follow-up. There was no difference in requirement for mechanical ventilation between individuals treated with magnesium and those receiving placebo (odds ratio 0.71, 95% CI 0.36-1.40; p=0.324); survival was also much the same in the two groups. However, compared with the placebo group, patients receiving magnesium required significantly less midazolam (7.1 mg/kg per day [0.1-47.9] vs 1.4 mg/kg per day [0.0-17.3]; p=0.026) and pipecuronium (2.3 mg/kg per day [0.0-33.0] vs 0.0 mg/kg per day [0.0-14.8]; p=0.005) to control muscle spasms and associated tachycardia. Individuals receiving magnesium were 4.7 (1.4-15.9) times less likely to require verapamil to treat cardiovascular instability than those in the placebo group. The incidence of adverse events was not different between the groups. INTERPRETATION: Magnesium infusion does not reduce the need for mechanical ventilation in adults with severe tetanus but does reduce the requirement for other drugs to control muscle spasms and cardiovascular instability.